"Raumpatrouille": The Cold War, the "Citizen in Uniform," and West German Television. - Hantke, Steffen (Science Fiction Studies, 2004)
Kept in the public consciousness by a devoted fan following, the series "Raumpatrouille Orion," all seven episodes of which aired in 1966, stands as the first science fiction program produced by and for German television. With its critical exploration of insubordination in a military setting, the show reflects ambiguities among the German population about West Germany's role in NATO in the wake of German rearmament after World War II. At the same time, the show's critique of blind military obedience and its positive validation of insubordination prepared the way for a new form of competitive individualism. The program echoes central features of the brand of neoliberalism common in post-War West Germany.